Gestão da carreira docente e autonomia universitária: estudo acerca da colaboração esporádica do professor do magistério superior na Universidade Federal da Paraíba - Souza, Isaías Araújo de (2021)
This study aims to analyze the regulatory conditions of sporadic collaboration approved by UFPB, according to the general conditions of article 21 of Law 12.772/2012 and the normative experience of other IFES. In this way, this work uses university autonomy as its theoretical reference, including the work of authors such as Ranieri (2005), Durham (1989), Cunha (2005) and Chauí (2003). Also in the theoretical chapter, the career and teaching work of the Higher Magisterium were addressed, discussing the regime of exclusive dedication and sporadic collaboration, with emphasis on the authors Mancebo (2010), Sguissardi and Silva Júnior (2018), Mancebo, Maués and Chaves (2006) and Lemos (2011). This research is characterized as a case study with a qualitative approach and uses bibliographic and documentary research techniques, with objectives of exploratory - descriptive nature, with a time frame starting from 2012 onwards. A sample of 10 (ten) IFES was defined, where the two with the largest budgets per region of the country were included. Among the researched IFES, responses to the questionnaire applied through the Fala.BR platform showed that 4 (four) effectively regulated the object of investigation of this work. Once in possession of normative documents, a document content analysis was applied according to Bardin (1977), to analyze the collected information, with a subsequent comparative analysis of the examined contents. From the results, it was possible to conclude that UFPB made progress in the treatment of sporadic collaboration, establishing specific conditions that guarantee the conduction of the authorization process of sporadic activities by the Institution. However, the approved regulatory conditions of sporadic collaboration present weaknesses subject to review by CONSEPE/UFPB.